2015
DOI: 10.1016/j.compbiomed.2014.12.006
|View full text |Cite
|
Sign up to set email alerts
|

A virtual reality based simulator for learning nasogastric tube placement

Abstract: Nasogastric tube (NGT) placement is a common clinical procedure where a plastic tube is inserted into the stomach through the nostril for feeding or drainage. However, the placement is a blind process in which the tube may be mistakenly inserted into other locations, leading to unexpected complications or fatal incidents. The placement techniques are conventionally acquired by practising on unrealistic rubber mannequins or on humans. In this paper, a virtual reality based training simulation system is proposed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0
6

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 37 publications
0
18
0
6
Order By: Relevance
“…The implementation of nursing education policy as a vehicle for achieving a better balance between the qualifications of nurses and national health care needs could result in great return on investment. Choi et al [98] in their study proposed a reality-based training simulation of tube insertion to facilitate NGT placement and showed that this system provides a new educational tool in order to enhance conventional NGT placement. The same group, in another study, explained a method for developing a computerized NGT placement training method for clinical education [99] Reisenberg et al [100] used a modified Delphi method to create a checklist for education and the assessment of NGT insertion and showed that using a validated checklist could decrease costs and complications while increasing the quality of health care.…”
Section: Educationmentioning
confidence: 99%
“…The implementation of nursing education policy as a vehicle for achieving a better balance between the qualifications of nurses and national health care needs could result in great return on investment. Choi et al [98] in their study proposed a reality-based training simulation of tube insertion to facilitate NGT placement and showed that this system provides a new educational tool in order to enhance conventional NGT placement. The same group, in another study, explained a method for developing a computerized NGT placement training method for clinical education [99] Reisenberg et al [100] used a modified Delphi method to create a checklist for education and the assessment of NGT insertion and showed that using a validated checklist could decrease costs and complications while increasing the quality of health care.…”
Section: Educationmentioning
confidence: 99%
“…Simulation technologies for NGT insertion are widely accepted for use in educational applications [2831]. The present research also evaluated whether training in nasogastric tube insertion with visual guidance versus blind insertions could result in different perceptions of insertions or skill acquisition in NGT insertion.…”
Section: Discussionmentioning
confidence: 99%
“…The method proposed here is compared with a physics-based model developed based on nonlinear FEM [4], where the insertion forces of a tube being inserted from the nostril to the laryngopharynx at a constant speed is simulated offline, and the wall of the passage is modeled as rigid body. In Fig.…”
Section: Comparison With Physics-based Modelmentioning
confidence: 99%
“…Besides, the computation also needs to be fast enough, at a refresh rate of 1 kHz, in order to simulate the haptic feedback in a smooth and natural way. Nevertheless, haptic simulation using computation-intensive methods like FEM can be achieved in real time with the better hardware available nowadays or using alternative approaches [4]. Despite the theoretical rigor, the physics-based approaches still require accurate identification of the model parameters for realistic simulation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation